Fresh-keeping functional water-based master batch suitable for paper pulp molding and preparation method and application of fresh-keeping functional water-based master batch
By developing fresh-preserving functional aqueous masterbatches suitable for pulp molding, nanocomposite antibacterial agents and organic gas adsorption materials are prepared using nano-grade grinding and spray drying technology, the problem of lack of fresh-preserving functions of pulp molded packaging products is solved, and effective fruit and vegetable fresh-preservation and antibacterial and mildew-proof effects are achieved.
Patent Information
- Application Number
- CN202411781458.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-07
AI Technical Summary
Existing pulp molded packaging products lack effective preservation function, and their fiber structure is not strong tolerant of water, and are easily damaged by moisture caused by respiration and transpiration of fruits and vegetables.
Develop a fresh-preserving functional aqueous masterbatch suitable for pulp molding, and prepare nanocomposite antibacterial agents and organic gas adsorption materials through nano-scale grinding and spray drying technology, combining aqueous resins and surfactants to form a coating with fresh-preserving effect.
It realizes effective fresh preservation of pulp molded packaging products, enhances antibacterial and mildew resistance, improves the film-forming and hydrophobicity of the coating, extends the fresh preservation time of fruits and vegetables, and complies with food safety testing standards.
Smart Images

Figure SMS_1 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of food preservation, in particular to a water-based masterbatch with a freshness-preserving function suitable for pulp molding, and a preparation method and application thereof. Background Art
[0002] At present, the packaging of fruits and vegetables during transportation and sales is still mainly plastic packaging that provides simple protection. In addition to not being very helpful in preserving fruits and vegetables, it also aggravates environmental pollution and other problems. With increasing attention paid to the negative impact of traditional plastic packaging on the environment, the demand for new healthy and environmentally friendly packaging materials has further increased, and biodegradable and recyclable pulp molded packaging products made from renewable resources are one of them.
[0003] Pulp molded packaging products are mainly made of degradable bagasse, waste paper, etc. They have good shockproof and impactproof properties, light weight, high compressive strength, etc. They have the advantages of little environmental pollution, environmental protection, biodegradability, and recyclability.
[0004] Pulp molded packaging products themselves do not have a preservation function. When used as packaging for fruits and vegetables, they lack effective preservation effects. What is easier to achieve in the entire processing procedure is to spray a layer of preservation coating on the inner surface of the pulp after molding as a functional layer. In order to ensure smooth production and not block the nozzle, the particle size of the slurry needs to be fine enough to meet the use requirements. The fiber structure of the pulp molded packaging products itself is not water-resistant, and the coating still needs a certain degree of hydrophobicity for protection to prevent the water generated by the respiration and transpiration of fruits and vegetables from damaging the pulp molded packaging products. For the preservation of fruits and vegetables, the required preservation materials must meet food contact standards, and there is currently a lack of such slurries on the market.
[0005] Therefore, it is necessary to design a water-based masterbatch with a fresh-keeping function suitable for pulp molding, and a preparation method and application thereof. Summary of the invention
[0006] In order to overcome the defects in the prior art, a water-based masterbatch with freshness-keeping function suitable for pulp molding and a preparation method and application thereof are provided.
[0007] The present invention is achieved through the following scheme:
[0008] A water-based masterbatch with a fresh-keeping function suitable for pulp molding, wherein the fresh-keeping function masterbatch comprises the following components in parts by mass:
[0009]
[0010]
[0011] The water-based resin is at least one or more of acrylate emulsion, water-based pure acrylate emulsion, acrylic acid-acrylate copolymer emulsion, and acrylic acid-acrylic acid copolymer modified emulsion.
[0012] The nano composite antibacterial agent is at least one or more of nano titanium dioxide, magnesium silicate, sorbic acid, sodium boric oxide, borax, methyl parahydroxybenzoate and sodium thiosulfate.
[0013] The organic gas adsorption material is at least one or more of silicon dioxide, modified starch, silica gel, zeolite, sodium magnesium lithium silicate, and kaolin.
[0014] The viscosity modifier is at least one or more of bentonite, ethyl cellulose, hydroxyethyl cellulose and hydroxypropyl cellulose.
[0015] The dispersant is at least one or more of acrylic acid copolymer and glycerol;
[0016] The lubricant is at least one or more of alkyl-modified silicone oil, butyl octadecanoate, and polyacrylamide;
[0017] The surfactant is at least one or more of cetearyl alcohol polyether, ethoxylated castor oil, and sodium octyl succinate sulfonate;
[0018] The emulsifier is at least one or more of sorbitan tristearate, polyoxyethylene sorbitan monostearate, and polyoxyethylene sorbitan tristearate;
[0019] The wetting agent is at least one or two of sodium dodecylbenzene sulfonate and polydimethylsiloxane.
[0020] The leveling agent is at least one or more of dodecanol, polyethylene glycol, and polyurethane leveling agents;
[0021] The defoaming agent is at least one or two of an organosilicon defoaming agent and an organic-acetylene defoaming agent.
[0022] The average particle size of the fresh-keeping functional water-based masterbatch suitable for pulp molding is 0.1-50 nm.
[0023] A method for preparing a water-based masterbatch with a fresh-keeping function suitable for pulp molding, the method comprising the following steps:
[0024] S1. The nano-composite antibacterial agent and ultrapure water were added to a food-grade coating-type horizontal zirconia three-roll mill, the roller pitch was adjusted to 3-5 microns, and the speed was 50-1200r / min for grinding for 0.5-5h. After grinding, the microfiltration was performed through a microporous membrane, and the filtrate was a micron-grade nano-composite antibacterial agent solution;
[0025] S2. The micron-sized nanocomposite antibacterial agent solution obtained in step S1 is subjected to a nano-sized zirconium oxide sand mill at a speed of 50-3300 r / min for 1-10 h, and the sand milling is stopped after the particle size reaches the standard of 0.1-50 nm, and the filtrate is filtered and separated with an ultrafiltration membrane to obtain a nanocomposite antibacterial agent solution;
[0026] S3. The nanocomposite antibacterial agent solution obtained in step S2 is dried by a nano-scale spray dryer at a pressure of 10-70MPa and a temperature of 90°C-120°C to obtain a nanocomposite antibacterial agent;
[0027] S4. The organic gas adsorbent material and ultrapure water were added to a food-grade coating-type horizontal zirconia three-roll mill, the roller pitch was adjusted to 3-5 microns, and the speed was 50-1200r / min for grinding for 0.5-5h. After grinding, the microporous membrane was microfiltered to obtain a micron-sized organic gas adsorbent solution;
[0028] S5. The micron-sized organic gas adsorption material solution obtained in step S4 is subjected to a nano-sized zirconium oxide sand mill at a speed of 50-3300 r / min for 1-8 h, and after grinding, the solution is filtered and separated through an ultrafiltration membrane to obtain a nano-sized organic gas adsorption material solution;
[0029] S6. The nanoscale organic gas adsorption material solution obtained in step S5 is dried in a nanoscale spray dryer at a pressure of 15-80MPa and a temperature of 85°C-120°C to obtain a nanoscale organic gas adsorption material;
[0030] S7. The nanocomposite antibacterial agent obtained in step S3 and the nanoscale organic gas adsorption material obtained in step S6 are stirred and dispersed in a high-speed stirrer at a stirring speed of 500-2500 r / min for 5-60 min to obtain a mixed material A;
[0031] S8. Ultrapure water, water-based resin, viscosity modifier and dispersant were sequentially added to the reactor for thorough mixing and dispersion, with a stirring speed of 100-800 r / min for 15-20 min, and then stirred and microfiltered through a microporous membrane to remove large particles to obtain a mixed material B solution;
[0032] S9. Add lubricant, surfactant, emulsifier, wetting agent, leveling agent and defoamer to a vertical vortex liquid-liquid mixer, stir and mix for 15-60 min at a speed of 100-1800 r / min, a vortex intensity of 0.5-3 m / s and a temperature of 5-30° C. to obtain a mixed solution C;
[0033] S10. Add the mixed material A obtained in step S7 and the mixed material B solution obtained in step S8 to a horizontal zirconia vortex solid-liquid mixer, and stir and mix at a speed of 100-2000 r / min, a vortex intensity of 0.3-3.2 m / s, and a temperature of 5-30°C for 1-6 hours to obtain a mixed solution D;
[0034] S11. Add the mixed solution D of step S10 into a nano-scale zirconium oxide sand mill, grind and disperse at a speed of 50-3300 r / min for 0.5-10 h, and add the mixed solution C obtained in step S9 into five equal parts five times during the grinding process. After grinding, filter and separate through a nanofiltration membrane, and bucket the filtrate to obtain a water-based masterbatch with a fresh-keeping function suitable for pulp molding.
[0035] An application of a water-based masterbatch with a fresh-keeping function suitable for pulp molding, wherein the water-based masterbatch with a fresh-keeping function suitable for pulp molding is used to prepare a pulp molded packaging product with a fresh-keeping effect, and the specific steps are:
[0036] S12. Place the water-based masterbatch with fresh-keeping function obtained in step S11 in the barrel of the automatic sprayer, and set the parameters of the automatic sprayer;
[0037] S13. The automatic spraying machine uses an ultra-fine atomizing nozzle with an aperture of 0.05mm-0.1mm. The spraying angle of the ultra-fine atomizing nozzle for spraying the plane of the pulp molded packaging product is set to 80°-100°, and the spraying angle of the ultra-fine atomizing nozzle for spraying the left and right sides is set to 15°-45°. The three nozzles are connected in parallel on the same track, and the movement speed of the spray gun is set to 3-10m / min;
[0038] S14. Further, the spraying distance is set to 15-25 cm and the spraying pressure is set to 3-8 bar;
[0039] S15. Further, the slurry flow rate is set to 30-200mL / min, and the spraying thickness is set to 3-60um;
[0040] S16. Further, the oven temperature is set to 80-120°C, and the drying time is set to 10-180s;
[0041] S17. Start the automatic spraying machine to evenly spray the water-based masterbatch with fresh-keeping function on the inner surface of the pulp molded packaging product, and obtain the pulp molded packaging product with fresh-keeping function after uniform film formation and drying.
[0042] The beneficial effects of the present invention are:
[0043] 1. The preparation method of the water-based masterbatch with a fresh-keeping function suitable for pulp molding of the present invention is simple, the materials are easily available, the slurry has good stability, excellent antibacterial and mildew-proof properties, good film-forming properties, strong hydrophobic effect, and meets food safety testing standards. The production process of the pulp molded packaging product itself does not need to be adjusted, and only the molded pulp molded packaging product is sprayed to form a layer of coating with a fresh-keeping effect, which has no effect on the performance of the pulp molded packaging product itself.
[0044] 2. The water-based masterbatch with fresh-keeping function suitable for pulp molding of the present invention mainly takes antibacterial and mildew-proofing and organic gas adsorption as the main directions, has good film-forming properties, and the fresh-keeping coating formed is smooth. While meeting the national standard for food contact materials, its preparation process is simple and efficient.
[0045] 3. A large amount of inorganic antibacterial ions are present in the water-based masterbatch with preservation function suitable for pulp molding of the present invention. In the pulp molded packaging products, the metal ions in the coating react with harmful microorganisms on the surface of fruits and vegetables, causing the destruction of their inherent components or functional disorders. When a trace amount of metal ions reaches the microbial cell membrane, the two are firmly adsorbed by the effect of Coulomb attraction. The metal ions penetrate the cell wall and enter the cell, react with the sulfhydryl group, and coagulate the protein, thereby destroying the activity of the microbial cell synthase, causing the cell to lose the ability to divide and reproduce and die. When the bacteria lose their activity, the metal ions will be freed from the bacteria and repeat the sterilization activity, so the antibacterial effect is long-lasting.
[0046] 4. The present invention provides a water-based masterbatch with a fresh-keeping function suitable for pulp molding, wherein a variety of adsorptive materials exist, which act synergistically with each other and can adsorb gases such as ethylene to a certain extent, while the photocatalytic reaction of inorganic metal ions can also decompose ethylene to a certain extent.
[0047] 5. The water-based masterbatch with a fresh-keeping function suitable for pulp molding of the present invention has a porous property, and the nano-composite antibacterial agent, surfactant, and emulsifier loaded therein play a sustained release role, further enhancing the antibacterial duration; and the surfactant and emulsifier therein play a continuous hydrophobic role, so that the water from the respiration and transpiration of fruits and vegetables will not penetrate into the internal fibers of the pulp molded packaging products to damage the pulp molded packaging products.
[0048] 6. The particle size of the water-based masterbatch with fresh-keeping function suitable for pulp molding of the present invention is 0.1-50nm. When spraying pulp molded packaging products, an ultra-fine atomizing nozzle with a smaller aperture can be used, and the nozzle is not easily blocked during spraying; a larger spraying pressure can be used, and the coating formed is more uniform. DETAILED DESCRIPTION
[0049] The preferred embodiments of the present invention are further described below:
[0050] A water-based masterbatch with a fresh-keeping function suitable for pulp molding, wherein the fresh-keeping function masterbatch comprises the following components in parts by mass:
[0051]
[0052]
[0053] According to the safety standards and compliance requirements of food contact materials and products in GB4806 National Food Safety Standard, the use of additives in food contact materials and products shall comply with the provisions of GB9685-2016 "Standards for the Use of Additives in Food Contact Materials and Products" and related announcements. The above-mentioned water-based resins, nano-composite antibacterial agents, organic gas adsorption materials, viscosity modifiers, dispersants, lubricants, surfactants, emulsifiers, wetting agents, leveling agents, and defoaming agents in this application all comply with the additives and usage requirements allowed in Table A.2 of GB9685-2016 for food contact coatings and coatings, and the scope of use and usage amount comply with this standard.
[0054] The water-based resin is at least one or more of acrylate emulsion, water-based pure acrylate emulsion, acrylic acid-acrylate copolymer emulsion, and acrylic acid-acrylic acid copolymer modified emulsion.
[0055] The nano composite antibacterial agent is at least one or more of nano titanium dioxide, magnesium silicate, sorbic acid, sodium boric oxide, borax, methyl parahydroxybenzoate and sodium thiosulfate.
[0056] The organic gas adsorption material is at least one or more of silicon dioxide, modified starch, silica gel, zeolite, sodium magnesium lithium silicate, and kaolin.
[0057] The viscosity modifier is at least one or more of bentonite, ethyl cellulose, hydroxyethyl cellulose and hydroxypropyl cellulose.
[0058] The dispersant is at least one or more of acrylic acid copolymer and glycerol;
[0059] The lubricant is at least one or more of alkyl-modified silicone oil, butyl octadecanoate, and polyacrylamide;
[0060] The surfactant is at least one or more of cetearyl alcohol polyether, ethoxylated castor oil, and sodium octyl succinate sulfonate;
[0061] The emulsifier is at least one or more of sorbitan tristearate, polyoxyethylene sorbitan monostearate, and polyoxyethylene sorbitan tristearate;
[0062] The wetting agent is at least one or two of sodium dodecylbenzene sulfonate and polydimethylsiloxane.
[0063] The leveling agent is at least one or more of dodecanol, polyethylene glycol, and polyurethane leveling agents;
[0064] The defoaming agent is at least one or two of an organosilicon defoaming agent and an organic-acetylene defoaming agent.
[0065] The average particle size of the fresh-keeping functional water-based masterbatch suitable for pulp molding is 0.1-50 nm.
[0066] A method for preparing a water-based masterbatch with a fresh-keeping function suitable for pulp molding, the method comprising the following steps:
[0067] S1. The nano-composite antibacterial agent and ultrapure water were added to a food-grade coating-type horizontal zirconia three-roll mill, the roller pitch was adjusted to 3-5 microns, and the speed was 50-1200r / min for grinding for 0.5-5h. After grinding, the microfiltration was performed through a microporous membrane, and the filtrate was a micron-grade nano-composite antibacterial agent solution;
[0068] S2. The micron-sized nanocomposite antibacterial agent solution obtained in step S1 is subjected to a nano-sized zirconium oxide sand mill at a speed of 50-3300 r / min for 1-10 h, and the sand milling is stopped after the particle size reaches the standard of 0.1-50 nm, and the filtrate is filtered and separated with an ultrafiltration membrane to obtain a nanocomposite antibacterial agent solution;
[0069] S3. The nanocomposite antibacterial agent solution obtained in step S2 is dried by a nano-scale spray dryer at a pressure of 10-70MPa and a temperature of 90°C-120°C to obtain a nanocomposite antibacterial agent;
[0070] S4. The organic gas adsorbent material and ultrapure water were added to a food-grade coating-type horizontal zirconia three-roll mill, the roller pitch was adjusted to 3-5 microns, and the speed was 50-1200r / min for grinding for 0.5-5h. After grinding, the microporous membrane was microfiltered to obtain a micron-sized organic gas adsorbent solution;
[0071] S5. The micron-sized organic gas adsorption material solution obtained in step S4 is subjected to a nano-sized zirconium oxide sand mill at a speed of 50-3300 r / min for 1-8 h, and after grinding, the solution is filtered and separated through an ultrafiltration membrane to obtain a nano-sized organic gas adsorption material solution;
[0072] S6. The nanoscale organic gas adsorption material solution obtained in step S5 is dried in a nanoscale spray dryer at a pressure of 15-80MPa and a temperature of 85°C-120°C to obtain a nanoscale organic gas adsorption material;
[0073] S7. The nanocomposite antibacterial agent obtained in step S3 and the nanoscale organic gas adsorption material obtained in step S6 are stirred and dispersed in a high-speed stirrer at a stirring speed of 500-2500 r / min for 5-60 min to obtain a mixed material A;
[0074] S8. Ultrapure water, water-based resin, viscosity modifier and dispersant were sequentially added to the reactor for thorough mixing and dispersion, with a stirring speed of 100-800 r / min for 15-20 min, and then stirred and microfiltered through a microporous membrane to remove large particles to obtain a mixed material B solution;
[0075] S9. Add lubricant, surfactant, emulsifier, wetting agent, leveling agent and defoamer to a vertical vortex liquid-liquid mixer, stir and mix for 15-60 min at a speed of 100-1800 r / min, a vortex intensity of 0.5-3 m / s and a temperature of 5-30° C. to obtain a mixed solution C;
[0076] S10. Add the mixed material A obtained in step S7 and the mixed material B solution obtained in step S8 to a horizontal zirconia vortex solid-liquid mixer, and stir and mix at a speed of 100-2000 r / min, a vortex intensity of 0.3-3.2 m / s, and a temperature of 5-30°C for 1-6 hours to obtain a mixed solution D;
[0077] S11. Add the mixed solution D of step S10 into a nano-scale zirconium oxide sand mill, grind and disperse at a speed of 50-3300 r / min for 0.5-10 h, and add the mixed solution C obtained in step S9 into five equal parts five times during the grinding process. After grinding, filter and separate through a nanofiltration membrane, and bucket the filtrate to obtain a water-based masterbatch with a fresh-keeping function suitable for pulp molding.
[0078] An application of a water-based masterbatch with a fresh-keeping function suitable for pulp molding, wherein the water-based masterbatch with a fresh-keeping function suitable for pulp molding is used to prepare a pulp molded packaging product with a fresh-keeping effect, and the specific steps are:
[0079] S12. Place the water-based masterbatch with fresh-keeping function obtained in step S11 in the barrel of the automatic sprayer, and set the parameters of the automatic sprayer;
[0080] S13. The automatic spraying machine uses an ultra-fine atomizing nozzle with an aperture of 0.05mm-0.1mm. The spraying angle of the ultra-fine atomizing nozzle for spraying the plane of the pulp molded packaging product is set to 80°-100°, and the spraying angle of the ultra-fine atomizing nozzle for spraying the left and right sides is set to 15°-45°. The three nozzles are connected in parallel on the same track, and the movement speed of the spray gun is set to 3-10m / min;
[0081] S14. Further, the spraying distance is set to 15-25 cm and the spraying pressure is set to 3-8 bar;
[0082] S15. Further, the slurry flow rate is set to 30-200mL / min, and the spraying thickness is set to 3-60um;
[0083] S16. Further, the oven temperature is set to 80-120°C, and the drying time is set to 10-180s;
[0084] S17. Start the automatic spraying machine to evenly spray the water-based masterbatch with fresh-keeping function on the inner surface of the pulp molded packaging product, and obtain the pulp molded packaging product with fresh-keeping function after uniform film formation and drying.
[0085] The present application is further described below in conjunction with specific embodiments:
[0086] Example 1
[0087] S1. Add 5 parts of nano-titanium dioxide, 3 parts of sorbic acid, 3 parts of borax, 4 parts of sodium thiosulfate and 40 parts of ultrapure water to a food-grade coating-type horizontal zirconia three-roll grinder, adjust the roller spacing to 3-5 microns, grind at a speed of 50-1200r / min for 0.5-5h, and after grinding, microfiltration is performed through a microporous filter membrane to obtain a filtrate of a micron-grade nano-composite antibacterial agent solution;
[0088] S2. The micron-sized nanocomposite antibacterial agent solution obtained in step S1 is subjected to a nano-sized zirconium oxide sand mill at a speed of 50-3300 r / min for 1-10 h, and the sand milling is stopped after the particle size reaches the standard of 0.1-50 nm, and the filtrate is filtered with an ultrafiltration membrane to obtain a nanocomposite antibacterial agent solution;
[0089] S3. The nanocomposite antibacterial agent solution obtained in step S2 is dried by a nano-scale spray dryer at a pressure of 10-70MPa and a temperature of 90°C-120°C to obtain a nanocomposite antibacterial agent;
[0090] S4. Add 6 parts of silicon dioxide, 3 parts of modified starch, 4 parts of sodium magnesium lithium silicate and 40 parts of ultrapure water to a food-grade coating-type horizontal zirconia three-roll mill, adjust the roller pitch to 3-5 microns, grind at a speed of 50-1200r / min for 0.5-5h, and after grinding, microfiltration is performed through a microporous filter membrane to obtain a filtrate obtained as a micron-sized organic gas adsorption material solution;
[0091] S5. The micron-sized organic gas adsorption material solution obtained in step S4 is subjected to a nano-sized zirconium oxide sand mill at a speed of 50-3300 r / min for 1-8 h, and after grinding, the solution is filtered and separated through an ultrafiltration membrane to obtain a nano-sized organic gas adsorption material solution;
[0092] S6. The nanoscale organic gas adsorption material solution obtained in step S5 is dried in a nanoscale spray dryer at a pressure of 15-80MPa and a temperature of 85°C-120°C to obtain a nanoscale organic gas adsorption material;
[0093] S7. The nanocomposite antibacterial agent obtained in step S3 above, 15 parts, the nanoscale organic gas adsorption material obtained in step S6, 13 parts, were stirred and dispersed in a high-speed stirrer at a stirring speed of 500-2500r / min for 5-60min to obtain a mixed material A;
[0094] S8. 40 parts of ultrapure water, 8 parts of acrylate emulsion, 5 parts of acrylic acid-acrylate copolymer emulsion, 2 parts of ethyl cellulose, 0.2 parts of acrylic acid copolymer and 0.6 parts of glycerol were added to the reactor for thorough mixing and dispersion, with a stirring speed of 100-800 r / min for 15-20 min. After stirring, the mixture was microfiltered through a microporous membrane to remove large particles to obtain a mixed material B solution;
[0095] S9. 0.3 parts of alkyl-modified silicone oil, 0.3 parts of butyl octadecanoate, 0.3 parts of cetearyl alcohol polyether, 0.5 parts of sodium succinate octyl sulfonate, 0.5 parts of sorbitan tristearate, 0.5 parts of polyoxyethylene sorbitan monostearate, 0.4 parts of sodium dodecylbenzene sulfonate, 0.3 parts of polydimethylsiloxane, 0.2 parts of dodecanol, 0.2 parts of polyurethane leveling agent, and 0.5 parts of silicone defoamer are added to a vertical vortex liquid-liquid mixer, and the mixture is stirred and mixed for 15-60 minutes at a speed of 100-1800 r / min, a vortex intensity of 0.5-3 m / s, and a temperature of 5-30° C. to obtain a mixed solution C;
[0096] S10. Add the mixed material A obtained in step S7 and the mixed material B solution obtained in step S8 to a horizontal zirconia vortex solid-liquid mixer, and stir and mix at a speed of 100-2000 r / min, a vortex intensity of 0.3-3.2 m / s, and a temperature of 5-30°C for 1-6 hours to obtain a mixed solution D;
[0097] S11. Add the mixed solution D of step S10 into a nano-scale zirconium oxide sand mill, grind and disperse at a speed of 50-3300 r / min for 0.5-10 h, and add the mixed solution C obtained in step S9 into five equal parts five times during the grinding process. After grinding, filter and separate through a nanofiltration membrane, and bucket the filtrate to obtain a water-based masterbatch with a fresh-keeping function suitable for pulp molding.
[0098] S12. Place the water-based masterbatch with fresh-keeping function obtained in step S11 in the barrel of the automatic sprayer, and set the parameters of the automatic sprayer;
[0099] S13. The automatic spraying machine uses an ultra-fine atomizing nozzle with an aperture of 0.05mm-0.1mm. The spraying angle of the ultra-fine atomizing nozzle for spraying the surface of the pulp molded packaging product is set to 80°-100°, and the spraying angle of the ultra-fine atomizing nozzle for spraying the left and right sides is set to 15°-45°. The three nozzles are connected in parallel on the same track, and the moving speed of the spray gun is set to 3-10m / min.
[0100] S14. Further, the spraying distance is set to 15-25 cm and the spraying pressure is set to 3-8 bar;
[0101] S15. Further, the slurry flow rate is set to 30-200mL / min, and the spraying thickness is set to 3-60um;
[0102] S16. Further, the oven temperature is set to 80-120°C, and the drying time is set to 10-180s;
[0103] S17. Start the automatic spraying machine to evenly spray the water-based masterbatch with fresh-keeping function on the inner surface of the pulp molded packaging product, and obtain the pulp molded packaging product with fresh-keeping function after uniform film formation and drying.
[0104] Example 2
[0105] S1. 7 parts of magnesium silicate, 5 parts of sodium boric oxide, 3 parts of methyl paraben and 40 parts of ultrapure water were added to a food-grade coating-type horizontal zirconia three-roll mill, the roller pitch was adjusted to 3-5 microns, and the speed was 50-1200r / min for 0.5-5h. After grinding, microfiltration was performed through a microporous filter membrane to obtain a filtrate of a micron-scale nanocomposite antibacterial agent solution;
[0106] S2. The micron-sized nanocomposite antibacterial agent solution obtained in step S1 is subjected to a nano-sized zirconium oxide sand mill at a speed of 50-3300 r / min for 1-10 h, and the sand milling is stopped after the particle size reaches the standard of 0.1-50 nm, and the filtrate is filtered with an ultrafiltration membrane to obtain a nanocomposite antibacterial agent solution;
[0107] S3. The nanocomposite antibacterial agent solution obtained in step S2 is dried by a nano-scale spray dryer at a pressure of 10-70MPa and a temperature of 90°C-120°C to obtain a nanocomposite antibacterial agent;
[0108] S4. Add 5 parts of silica gel, 5 parts of zeolite, 3 parts of kaolin and 40 parts of ultrapure water to a food-grade coating-type horizontal zirconia three-roll mill, adjust the roller pitch to 3-5 microns, grind at a speed of 50-1200r / min for 0.5-5h, and after grinding, microfiltration was performed through a microporous membrane to obtain a filtrate obtained as a micron-sized organic gas adsorption material solution;
[0109] S5. The micron-sized organic gas adsorption material solution obtained in step S4 is subjected to a nano-sized zirconium oxide sand mill at a speed of 50-3300 r / min for 1-8 h, and after grinding, the solution is filtered and separated through an ultrafiltration membrane to obtain a nano-sized organic gas adsorption material solution;
[0110] S6. The nanoscale organic gas adsorption material solution obtained in step S5 is dried in a nanoscale spray dryer at a pressure of 15-80MPa and a temperature of 85°C-120°C to obtain a nanoscale organic gas adsorption material;
[0111] S7. The nanocomposite antibacterial agent obtained in step S3 above, 15 parts, the nanoscale organic gas adsorption material obtained in step S6, 13 parts, were stirred and dispersed in a high-speed stirrer at a stirring speed of 500-2500r / min for 5-60min to obtain a mixed material A;
[0112] S8. 40 parts of ultrapure water, 6 parts of aqueous pure acrylate emulsion, 7 parts of acrylic acid-acrylic acid copolymer modified emulsion, 2 parts of hydroxypropyl cellulose, 0.2 parts of acrylic acid copolymer, and 0.6 parts of glycerol were added to the reactor for thorough mixing and dispersion, with a stirring speed of 100-800r / min for 15-20min. After stirring, the mixture was microfiltered through a microporous filter membrane to remove large particles to obtain a mixed material B solution;
[0113] S9. 0.3 parts of alkyl-modified silicone oil, 0.3 parts of butyl octadecanoate, 0.3 parts of cetearyl alcohol polyether, 0.5 parts of sodium succinate octyl sulfonate, 0.5 parts of sorbitan tristearate, 0.5 parts of polyoxyethylene sorbitan monostearate, 0.4 parts of sodium dodecylbenzene sulfonate, 0.3 parts of polydimethylsiloxane, 0.2 parts of dodecanol, 0.2 parts of polyurethane leveling agent, and 0.5 parts of organic-acetylene defoaming agent are added to a vertical vortex liquid-liquid mixer, and the mixture is stirred and mixed for 15-60 minutes at a speed of 100-1800 r / min, a vortex intensity of 0.5-3 m / s, and a temperature of 5-30° C. to obtain a mixed solution C;
[0114] S10. Add the mixed material A obtained in step S7 and the mixed material B solution obtained in step S8 to a horizontal zirconia vortex solid-liquid mixer, and stir and mix at a speed of 100-2000 r / min, a vortex intensity of 0.3-3.2 m / s, and a temperature of 5-30°C for 1-6 hours to obtain a mixed solution D;
[0115] S11. Add the mixed solution D of step S10 into a nano-scale zirconium oxide sand mill, grind and disperse at a speed of 50-3300 r / min for 0.5-10 h, and add the mixed solution C obtained in step S9 into five equal parts five times during the grinding process. After grinding, filter and separate through a nanofiltration membrane, and bucket the filtrate to obtain a water-based masterbatch with a fresh-keeping function suitable for pulp molding.
[0116] S12. Place the water-based masterbatch with fresh-keeping function obtained in step S11 in the barrel of the automatic sprayer, and set the parameters of the automatic sprayer;
[0117] S13. The automatic spraying machine uses an ultra-fine atomizing nozzle with an aperture of 0.05mm-0.1mm. The spraying angle of the ultra-fine atomizing nozzle for spraying the surface of the pulp molded packaging product is set to 80°-100°, and the spraying angle of the ultra-fine atomizing nozzle for spraying the left and right sides is set to 15°-45°. The three nozzles are connected in parallel on the same track, and the moving speed of the spray gun is set to 3-10m / min.
[0118] S14. Further, the spraying distance is set to 15-25 cm and the spraying pressure is set to 3-8 bar;
[0119] S15. Further, the slurry flow rate is set to 30-200mL / min, and the spraying thickness is set to 3-60um;
[0120] S16. Further, the oven temperature is set to 80-120°C, and the drying time is set to 10-180s;
[0121] S17. Start the automatic spraying machine to evenly spray the water-based masterbatch with fresh-keeping function on the inner surface of the pulp molded packaging product, and obtain the pulp molded packaging product with fresh-keeping function after uniform film formation and drying.
[0122] Comparative Example 1
[0123] S1. Add 5 parts of nano-titanium dioxide, 3 parts of sorbic acid, 3 parts of Kathon, 4 parts of sodium thiosulfate and 40 parts of ultrapure water to a food-grade coating-type horizontal zirconia three-roll grinder, adjust the roller spacing to 3-5 microns, grind at a speed of 50-1200r / min for 0.5-5h, stop sanding after the particle size reaches the standard of 0.1-50nm, and microfilter through a microporous filter membrane to obtain a filtrate of a micron-grade nano-composite antibacterial agent solution;
[0124] S2. The micron-sized nanocomposite antibacterial agent solution obtained in step S1 is subjected to a nano-sized zirconium oxide sand mill at a speed of 50-3300 r / min for 1-10 h, and after grinding, the mixture is filtered with an ultrafiltration membrane to obtain a nanocomposite antibacterial agent solution;
[0125] S3. The nanocomposite antibacterial agent solution obtained in step S2 is dried by a nano-scale spray dryer at a pressure of 10-70MPa and a temperature of 90°C-120°C to obtain a nanocomposite antibacterial agent;
[0126] S4. 15 parts of the nanocomposite antibacterial agent obtained in step S3 above, 6 parts of silicon dioxide, 3 parts of modified starch, and 4 parts of sodium magnesium lithium silicate were stirred and dispersed in a high-speed mixer at a stirring speed of 500-2500r / min for 5-60min to obtain a mixed material A;
[0127] S5. 40 parts of ultrapure water, 8 parts of acrylate emulsion, 5 parts of acrylic acid-acrylate copolymer emulsion, 2 parts of ethyl cellulose, 0.2 parts of acrylic acid copolymer and 0.6 parts of glycerol were added to the reactor for thorough mixing and dispersion, with a stirring speed of 100-800 r / min for 15-20 min. After stirring, the mixture was microfiltered through a microporous membrane to remove large particles to obtain a mixed material B solution;
[0128] S6. 0.3 parts of alkyl-modified silicone oil, 0.3 parts of butyl octadecanoate, 0.3 parts of cetearyl alcohol polyether, 0.5 parts of sodium succinate octyl sulfonate, 0.2 parts of dodecanol, 0.2 parts of polyurethane leveling agent, and 0.5 parts of silicone defoamer are added to a vertical vortex liquid-liquid mixer, and the mixture is stirred and mixed for 15-60 minutes at a speed of 100-1800 r / min, a vortex intensity of 0.5-3 m / s, and a temperature of 5-30° C. to obtain a mixed solution C;
[0129] S7. Add the mixed material A obtained in step S4 and the mixed material B solution obtained in step S5 to a horizontal zirconia vortex solid-liquid mixer, and stir and mix at a speed of 100-2000 r / min, a vortex intensity of 0.3-3.2 m / s, and a temperature of 5-30°C for 1-6 h to obtain a mixed solution D;
[0130] S8. Add the mixed solution D obtained in the above step S7 into a nano-scale zirconium oxide sand mill, grind and disperse at a speed of 50-3300r / min for 0.5-10h, during which the mixed solution C obtained in the above step S6 is added 5 times in five equal portions, and after grinding, the mixed solution is separated by filtering with a nanofiltration membrane, and the filtrate is barreled to obtain a water-based masterbatch.
[0131] S9. Place the water-based masterbatch obtained in step S8 in the barrel of the automatic sprayer and set the parameters of the automatic sprayer;
[0132] S10. The automatic spraying machine uses an ultra-fine atomizing nozzle with an aperture of 0.05mm-0.1mm. The spraying angle of the ultra-fine atomizing nozzle for spraying the surface of the pulp molded packaging product is set to 80°-100°, and the spraying angle of the ultra-fine atomizing nozzle for spraying the left and right sides is set to 15°-45°. The three nozzles are connected in parallel on the same track, and the moving speed of the spray gun is set to 3-10m / min.
[0133] S11. Further, the spraying distance is set to 15-25 cm and the spraying pressure is set to 3-8 bar;
[0134] S12. Further, the slurry flow rate is set to 30-200mL / min, and the spraying thickness is set to 3-60um;
[0135] S13. Further, the oven temperature is set to 80-120°C, and the drying time is set to 10-180s;
[0136] S14. Start the automatic spraying machine to evenly spray the water-based masterbatch on the inner surface of the pulp molded packaging product, and obtain the pulp molded packaging product after even film formation and drying.
[0137] Comparative Example 2
[0138] S1. Add 6 parts of silicon dioxide, 3 parts of modified starch, 4 parts of sodium magnesium lithium silicate, and 40 parts of ultrapure water to a food-grade coating-type horizontal zirconia three-roll grinder, adjust the roller pitch to 3-5 microns, grind at a speed of 50-1200r / min for 0.5-5h, and after grinding, microfiltration is performed through a microporous filter membrane, and the filtrate obtained is a micron-grade organic gas adsorption material solution;
[0139] S2. The micron-sized organic gas adsorption material solution obtained in step S1 is subjected to a nano-sized zirconium oxide sand mill at a speed of 50-3300 r / min for 1-8 h, and after grinding, the solution is filtered and separated through an ultrafiltration membrane, and the filtrate obtained is a nano-sized organic gas adsorption material solution;
[0140] S3. The nanoscale organic gas adsorption material solution obtained in step S2 is dried in a nanoscale spray dryer at a pressure of 15-80MPa and a temperature of 85°C-120°C to obtain a nanoscale organic gas adsorption material;
[0141] S4. 5 parts of nano-titanium dioxide, 3 parts of sorbic acid, 3 parts of borax, 4 parts of sodium thiosulfate, and 13 parts of the nano-scale organic gas adsorption material obtained in step S3 were stirred and dispersed in a high-speed stirrer at a stirring speed of 500-2500r / min for 5-60min to obtain a mixed material A;
[0142] S5. 40 parts of ultrapure water, 8 parts of acrylate emulsion, 5 parts of acrylic acid-acrylate copolymer emulsion, 2 parts of ethyl cellulose, 0.2 parts of acrylic acid copolymer and 0.6 parts of glycerol were added to the reactor for thorough mixing and dispersion, with a stirring speed of 100-800 r / min for 15-20 min. After stirring, the mixture was microfiltered through a microporous membrane to remove large particles to obtain a mixed material B solution;
[0143] S6. 0.3 parts of alkyl-modified silicone oil, 0.3 parts of butyl octadecanoate, 0.3 parts of cetearyl alcohol polyether, 0.5 parts of sodium succinate octyl sulfonate, 0.5 parts of sorbitan tristearate, 0.5 parts of polyoxyethylene sorbitan monostearate, 0.4 parts of sodium dodecylbenzene sulfonate, 0.3 parts of polydimethylsiloxane, 0.2 parts of dodecanol, 0.2 parts of polyurethane leveling agent, and 0.5 parts of silicone defoamer are added to a vertical vortex liquid-liquid mixer, and the mixture is stirred and mixed for 15-60 minutes at a speed of 100-1800 r / min, a vortex intensity of 0.5-3 m / s, and a temperature of 5-30° C. to obtain a mixed solution C;
[0144] S7. Add the mixed material A obtained in step S4 and the mixed material B solution obtained in step S5 to a horizontal zirconia vortex solid-liquid mixer, and stir and mix at a speed of 100-2000 r / min, a vortex intensity of 0.3-3.2 m / s, and a temperature of 5-30°C for 1-6 h to obtain a mixed solution D;
[0145] S8. Add the mixed solution D obtained in the above step S7 into a nano-scale zirconium oxide sand mill, grind and disperse at a speed of 50-3300r / min for 0.5-10h, during which the mixed solution C obtained in the above step S6 is added 5 times in five equal portions, and after grinding, the mixed solution is separated by filtering with a nanofiltration membrane, and the filtrate is barreled as water-based masterbatch.
[0146] S9. Place the water-based masterbatch obtained in step S8 in the barrel of the automatic sprayer and set the parameters of the automatic sprayer;
[0147] S10. The automatic spraying machine uses an ultra-fine atomizing nozzle with an aperture of 0.05mm-0.1mm. The spraying angle of the ultra-fine atomizing nozzle for spraying the surface of the pulp molded packaging product is set to 80°-100°, and the spraying angle of the ultra-fine atomizing nozzle for spraying the left and right sides is set to 15°-45°. The three nozzles are connected in parallel on the same track, and the moving speed of the spray gun is set to 3-10m / min.
[0148] S11. Further, the spraying distance is set to 15-25 cm and the spraying pressure is set to 3-8 bar;
[0149] S12. Further, the slurry flow rate is set to 30-200mL / min, and the spraying thickness is set to 3-60um;
[0150] S13. Further, the oven temperature is set to 80-120°C, and the drying time is set to 10-180s;
[0151] S14. Start the automatic spraying machine to evenly spray the water-based masterbatch on the inner surface of the pulp molded packaging product, and obtain the pulp molded packaging product after even film formation and drying.
[0152] Comparative Example 3
[0153] S1. Add 5 parts of nano-titanium dioxide, 3 parts of sorbic acid, 3 parts of Kathon, 4 parts of sodium thiosulfate and 40 parts of ultrapure water to a food-grade coating-type horizontal zirconia three-roll grinder, adjust the roller spacing to 3-5 microns, grind at a speed of 50-1200r / min for 0.5-5h, stop sanding after the particle size reaches the standard of 0.1-50nm, and microfilter through a microporous filter membrane to obtain a filtrate of a micron-grade nano-composite antibacterial agent solution;
[0154] S2. The micron-sized nanocomposite antibacterial agent solution obtained in step S1 is subjected to a nano-sized zirconium oxide sand mill at a speed of 50-3300 r / min for 1-10 h, and after grinding, the mixture is filtered with an ultrafiltration membrane to obtain a nanocomposite antibacterial agent solution;
[0155] S3. The nanocomposite antibacterial agent solution obtained in step S2 is dried by a nano-scale spray dryer at a pressure of 10-70MPa and a temperature of 90°C-120°C to obtain a nanocomposite antibacterial agent;
[0156] S4. 40 parts of ultrapure water, 8 parts of acrylate emulsion, 5 parts of acrylic acid-acrylate copolymer emulsion, 2 parts of ethyl cellulose, 0.2 parts of acrylic acid copolymer and 0.6 parts of glycerol were added to the reactor for thorough mixing and dispersion, with a stirring speed of 100-800 r / min for 15-20 min, and then stirred and microfiltered through a microporous membrane to remove large particles to obtain a mixed material A solution;
[0157] S5. 0.3 parts of alkyl-modified silicone oil, 0.3 parts of butyl octadecanoate, 0.3 parts of cetearyl alcohol polyether, 0.5 parts of sodium succinate octyl sulfonate, 0.2 parts of dodecanol, 0.2 parts of polyurethane leveling agent, and 0.5 parts of silicone defoamer are added to a vertical vortex liquid-liquid mixer, and the mixture is stirred and mixed for 15-60 minutes at a speed of 100-1800 r / min, a vortex intensity of 0.5-3 m / s, and a temperature of 5-30° C. to obtain a mixed solution B;
[0158] S6. 15 parts of nano-composite antibacterial agent, 6 parts of silicon dioxide, 3 parts of modified starch, 4 parts of sodium magnesium lithium silicate, and mixed material A solution were added to a vertical mixer, stirred and dispersed at a speed of 30-180r / min for 10-180min, and the mixed solution B was added 5 times in five equal parts during the period, and the water-based masterbatch was obtained by bucketing;
[0159] S7. Place the water-based masterbatch obtained in step S6 in the barrel of the automatic sprayer and set the parameters of the automatic sprayer;
[0160] S8. The automatic spraying machine uses an ultra-fine atomizing nozzle with an aperture of 0.05mm-0.1mm. The spraying angle of the ultra-fine atomizing nozzle for spraying the surface of the pulp molded packaging product is set to 80°-100°, and the spraying angle of the ultra-fine atomizing nozzle for spraying the left and right sides is set to 15°-45°. The three nozzles are connected in parallel on the same track, and the moving speed of the spray gun is set to 3-10m / min.
[0161] S9. Further, the spraying distance is set to 15-25 cm and the spraying pressure is set to 3-8 bar;
[0162] S10. Further, the slurry flow rate is set to 30-200mL / min, and the spraying thickness is set to 3-60um;
[0163] S11. Further, the oven temperature is set to 80-120°C, and the drying time is set to 10-180s;
[0164] S12. Start the automatic spraying machine to evenly spray the water-based masterbatch on the inner surface of the pulp molded packaging product, and obtain the pulp molded packaging product after even film formation and drying.
[0165] Comparative Example 4
[0166] S1. Add 6 parts of silicon dioxide, 3 parts of modified starch, 4 parts of sodium magnesium lithium silicate, and 40 parts of ultrapure water to a food-grade coating-type horizontal zirconia three-roll grinder, adjust the roller pitch to 3-5 microns, grind at a speed of 50-1200r / min for 0.5-5h, and after grinding, microfiltration is performed through a microporous filter membrane, and the filtrate obtained is a micron-grade organic gas adsorption material solution;
[0167] S2. The micron-sized organic gas adsorption material solution obtained in step S1 is subjected to a nano-sized zirconium oxide sand mill at a speed of 50-3300 r / min for 1-8 h, and after grinding, the solution is filtered and separated through an ultrafiltration membrane, and the filtrate obtained is a nano-sized organic gas adsorption material solution;
[0168] S3. The nanoscale organic gas adsorption material solution obtained in step S2 is dried in a nanoscale spray dryer at a pressure of 15-80MPa and a temperature of 85°C-120°C to obtain a nanoscale organic gas adsorption material;
[0169] S4. 40 parts of ultrapure water, 8 parts of acrylate emulsion, 5 parts of acrylic acid-acrylate copolymer emulsion, 2 parts of ethyl cellulose, 0.2 parts of acrylic acid copolymer and 0.6 parts of glycerol were added to the reactor for thorough mixing and dispersion, with a stirring speed of 100-800 r / min for 15-20 min, and then stirred and microfiltered through a microporous membrane to remove large particles to obtain a mixed material A solution;
[0170] S5. 0.3 parts of alkyl-modified silicone oil, 0.3 parts of butyl octadecanoate, 0.3 parts of cetearyl alcohol polyether, 0.5 parts of sodium succinate octyl sulfonate, 0.5 parts of sorbitan tristearate, 0.5 parts of polyoxyethylene sorbitan monostearate, 0.4 parts of sodium dodecylbenzene sulfonate, 0.3 parts of polydimethylsiloxane, 0.2 parts of dodecanol, 0.2 parts of polyurethane leveling agent, and 0.5 parts of silicone defoamer are added to a vertical vortex liquid-liquid mixer, and the mixture is stirred and mixed for 15-60 minutes at a speed of 100-1800 r / min, a vortex intensity of 0.5-3 m / s, and a temperature of 5-30° C. to obtain a mixed solution B;
[0171] S6. Add 5 parts of nano titanium dioxide, 3 parts of sorbic acid, 3 parts of borax, 4 parts of sodium thiosulfate, 13 parts of nano-scale organic gas adsorbent material, and mixed material A solution into a vertical mixer, stir and disperse at a speed of 30-180r / min for 10-180min, and add the mixed solution B 5 times in five equal parts during the period, and bucket to obtain a water-based masterbatch;
[0172] S7. Place the water-based masterbatch obtained in step S6 in the barrel of the automatic sprayer and set the parameters of the automatic sprayer;
[0173] S8. The automatic spraying machine uses an ultra-fine atomizing nozzle with an aperture of 0.05mm-0.1mm. The spraying angle of the ultra-fine atomizing nozzle for spraying the surface of the pulp molded packaging product is set to 80°-100°, and the spraying angle of the ultra-fine atomizing nozzle for spraying the left and right sides is set to 15°-45°. The three nozzles are connected in parallel on the same track, and the moving speed of the spray gun is set to 3-10m / min.
[0174] S9. Further, the spraying distance is set to 15-25 cm and the spraying pressure is set to 3-8 bar;
[0175] S10. Further, the slurry flow rate is set to 30-200mL / min, and the spraying thickness is set to 3-60um;
[0176] S11. Further, the oven temperature is set to 80-120°C, and the drying time is set to 10-180s;
[0177] S12. Start the automatic spraying machine to evenly spray the water-based masterbatch on the inner surface of the pulp molded packaging product, and obtain the pulp molded packaging product after uniform film formation and drying.
[0178] Comparative Example 5
[0179] S1. Add 5 parts of nano-titanium dioxide, 3 parts of sorbic acid, 3 parts of borax, 4 parts of sodium thiosulfate and 40 parts of ultrapure water to a food-grade coating-type horizontal zirconia three-roll grinder, adjust the roller spacing to 3-5 microns, grind at a speed of 50-1200r / min for 0.5-5h, and after grinding, microfiltration is performed through a microporous filter membrane to obtain a filtrate of a micron-grade nano-composite antibacterial agent solution;
[0180] S2. The micron-sized nanocomposite antibacterial agent solution obtained in step S1 is subjected to a nano-sized zirconium oxide sand mill at a speed of 50-3300 r / min for 1-10 h, and the sand milling is stopped after the particle size is detected to be 5-10 nm, and the filtrate is filtered with an ultrafiltration membrane to obtain a nanocomposite antibacterial agent solution;
[0181] S3. The nanocomposite antibacterial agent solution obtained in step S2 is dried by a nano-scale spray dryer at a pressure of 10-70MPa and a temperature of 90°C-120°C to obtain a nanocomposite antibacterial agent;
[0182] S4. Add 6 parts of silicon dioxide, 3 parts of modified starch, 4 parts of sodium magnesium lithium silicate and 40 parts of ultrapure water to a food-grade coating-type horizontal zirconia three-roll mill, adjust the roller pitch to 3-5 microns, grind at a speed of 50-1200r / min for 0.5-5h, and after grinding, microfiltration is performed through a microporous filter membrane to obtain a filtrate obtained as a micron-sized organic gas adsorption material solution;
[0183] S5. The micron-sized organic gas adsorption material solution obtained in step S4 is subjected to a nano-sized zirconium oxide sand mill at a speed of 50-3300 r / min for 1-8 h, and after grinding, the solution is filtered and separated through an ultrafiltration membrane to obtain a nano-sized organic gas adsorption material solution;
[0184] S6. The nanoscale organic gas adsorption material solution obtained in step S5 is dried in a nanoscale spray dryer at a pressure of 15-80MPa and a temperature of 85°C-120°C to obtain a nanoscale organic gas adsorption material;
[0185] S7. The nanocomposite antibacterial agent obtained in step S3 above, 15 parts, the nanoscale organic gas adsorption material obtained in step S6, 13 parts, were stirred and dispersed in a high-speed stirrer at a stirring speed of 500-2500r / min for 5-60min to obtain a mixed material A;
[0186] S8. 40 parts of ultrapure water, 8 parts of acrylate emulsion, 5 parts of acrylic acid-acrylate copolymer emulsion, 2 parts of ethyl cellulose, 0.2 parts of acrylic acid copolymer and 0.6 parts of glycerol were added to the reactor for thorough mixing and dispersion, with a stirring speed of 100-800 r / min for 15-20 min. After stirring, the mixture was microfiltered through a microporous membrane to remove large particles to obtain a mixed material B solution;
[0187] S9. 0.3 parts of alkyl-modified silicone oil, 0.3 parts of butyl octadecanoate, 0.3 parts of cetearyl alcohol polyether, 0.5 parts of sodium succinate octyl sulfonate, 0.2 parts of dodecanol, 0.2 parts of polyurethane leveling agent, and 0.5 parts of silicone defoamer are added to a vertical vortex liquid-liquid mixer, and the mixture is stirred and mixed for 15-60 minutes at a speed of 100-1800 r / min, a vortex intensity of 0.5-3 m / s, and a temperature of 5-30° C. to obtain a mixed solution C;
[0188] S10. Add the mixed material A obtained in step S7 and the mixed material B solution obtained in step S8 to a horizontal zirconia vortex solid-liquid mixer, and stir and mix at a speed of 100-2000 r / min, a vortex intensity of 0.3-3.2 m / s, and a temperature of 5-30°C for 1-6 hours to obtain a mixed solution D;
[0189] S11. Add the mixed solution D of step S10 into a nano-sized zirconium oxide sand mill, grind and disperse at a speed of 50-3300 r / min for 0.5-10 h, and add the mixed solution C obtained in step S9 into five equal portions for five times during the grinding process. After grinding, separate the mixture by filtering with a nanofiltration membrane, and bucket the filtrate to obtain a water-based masterbatch.
[0190] S12. Place the water-based masterbatch obtained in step S11 in the barrel of an automatic sprayer and set the parameters of the automatic sprayer;
[0191] S13. The automatic spraying machine uses an ultra-fine atomizing nozzle with an aperture of 0.05mm-0.1mm. The spraying angle of the ultra-fine atomizing nozzle for spraying the surface of the pulp molded packaging product is set to 80°-100°, and the spraying angle of the ultra-fine atomizing nozzle for spraying the left and right sides is set to 15°-45°. The three nozzles are connected in parallel on the same track, and the moving speed of the spray gun is set to 3-10m / min.
[0192] S14. Further, the spraying distance is set to 15-25 cm and the spraying pressure is set to 3-8 bar;
[0193] S15. Further, the slurry flow rate is set to 30-200mL / min, and the spraying thickness is set to 3-60um;
[0194] S16. Further, the oven temperature is set to 80-120°C, and the drying time is set to 10-180s;
[0195] S17. Start the automatic spraying machine to evenly spray the water-based masterbatch on the inner surface of the pulp molded packaging product, and obtain the pulp molded packaging product after even film formation and drying.
[0196] Comparative Example 6
[0197] S1. 7 parts of magnesium silicate, 5 parts of sodium boric oxide, 3 parts of methyl paraben and 40 parts of ultrapure water were added to a food-grade coating-type horizontal zirconia three-roll mill, the roller pitch was adjusted to 3-5 microns, and the speed was 50-1200r / min for 0.5-5h. After grinding, microfiltration was performed through a microporous filter membrane to obtain a filtrate of a micron-scale nanocomposite antibacterial agent solution;
[0198] S2. The micron-sized nanocomposite antibacterial agent solution obtained in step S1 is subjected to a nano-sized zirconium oxide sand mill at a speed of 50-3300 r / min for 1-10 h, and the sand milling is stopped after the particle size is detected to be 30-50 nm, and the filtrate is filtered with an ultrafiltration membrane to obtain a nanocomposite antibacterial agent solution;
[0199] S3. The nanocomposite antibacterial agent solution obtained in step S2 is dried by a nano-scale spray dryer at a pressure of 10-70MPa and a temperature of 90°C-120°C to obtain a nanocomposite antibacterial agent;
[0200] S4. Add 5 parts of silica gel, 5 parts of zeolite, 3 parts of kaolin and 40 parts of ultrapure water to a food-grade coating-type horizontal zirconia three-roll mill, adjust the roller pitch to 3-5 microns, grind at a speed of 50-1200r / min for 0.5-5h, and after grinding, microfiltration was performed through a microporous membrane to obtain a filtrate obtained as a micron-sized organic gas adsorption material solution;
[0201] S5. The micron-sized organic gas adsorption material solution obtained in step S4 is subjected to a nano-sized zirconium oxide sand mill at a speed of 50-3300 r / min for 1-8 h, and after grinding, the solution is filtered and separated through an ultrafiltration membrane to obtain a nano-sized organic gas adsorption material solution;
[0202] S6. The nanoscale organic gas adsorption material solution obtained in step S5 is dried in a nanoscale spray dryer at a pressure of 15-80MPa and a temperature of 85°C-120°C to obtain a nanoscale organic gas adsorption material;
[0203] S7. The nanocomposite antibacterial agent obtained in step S3 above, 15 parts, the nanoscale organic gas adsorption material obtained in step S6, 13 parts, were stirred and dispersed in a high-speed stirrer at a stirring speed of 500-2500r / min for 5-60min to obtain a mixed material A;
[0204] S8. 40 parts of ultrapure water, 6 parts of aqueous pure acrylate emulsion, 7 parts of acrylic acid-acrylic acid copolymer modified emulsion, 2 parts of hydroxypropyl cellulose, 0.2 parts of acrylic acid copolymer, and 0.6 parts of glycerol were added to the reactor for thorough mixing and dispersion, with a stirring speed of 100-800 r / min for 15-20 min. After stirring, the mixture was microfiltered through a microporous filter membrane to remove large particles to obtain a mixed material B solution;
[0205] S9. 0.3 parts of alkyl-modified silicone oil, 0.3 parts of butyl octadecanoate, 0.3 parts of cetearyl alcohol polyether, 0.5 parts of sodium succinate octyl sulfonate, 0.2 parts of dodecanol, 0.2 parts of polyurethane leveling agent, and 0.5 parts of organic-acetylene defoaming agent are added to a vertical vortex liquid-liquid mixer, and the mixture is stirred and mixed for 15-60 minutes at a speed of 100-1800 r / min, a vortex intensity of 0.5-3 m / s, and a temperature of 5-30° C. to obtain a mixed solution C;
[0206] S10. Add the mixed material A obtained in step S7 and the mixed material B solution obtained in step S8 to a horizontal zirconia vortex solid-liquid mixer, and stir and mix at a speed of 100-2000 r / min, a vortex intensity of 0.3-3.2 m / s, and a temperature of 5-30°C for 1-6 hours to obtain a mixed solution D;
[0207] S11. Add the mixed solution D of step S10 into a nano-sized zirconium oxide sand mill, grind and disperse at a speed of 50-3300 r / min for 0.5-10 h, and add the mixed solution C obtained in step S9 into five equal portions for five times during the grinding process. After grinding, separate the mixture by filtering with a nanofiltration membrane, and bucket the filtrate to obtain a water-based masterbatch.
[0208] S12. Place the water-based masterbatch obtained in step S11 in the barrel of an automatic sprayer and set the parameters of the automatic sprayer;
[0209] S13. The automatic spraying machine uses an ultra-fine atomizing nozzle with an aperture of 0.05mm-0.1mm. The spraying angle of the ultra-fine atomizing nozzle for spraying the surface of the pulp molded packaging product is set to 80°-100°, and the spraying angle of the ultra-fine atomizing nozzle for spraying the left and right sides is set to 15°-45°. The three nozzles are connected in parallel on the same track, and the moving speed of the spray gun is set to 3-10m / min.
[0210] S14. Further, the spraying distance is set to 15-25 cm and the spraying pressure is set to 3-8 bar;
[0211] S15. Further, the slurry flow rate is set to 30-200mL / min, and the spraying thickness is set to 3-60um;
[0212] S16. Further, the oven temperature is set to 80-120°C, and the drying time is set to 10-180s;
[0213] S17. Start the automatic spraying machine to evenly spray the water-based masterbatch on the inner surface of the pulp molded packaging product, and obtain the pulp molded packaging product after even film formation and drying.
[0214] Comparative Example 7
[0215] S1. 7 parts of magnesium silicate, 5 parts of sodium boric oxide, 3 parts of methyl paraben and 40 parts of ultrapure water were added to a food-grade coating-type horizontal zirconia three-roll mill, the roller pitch was adjusted to 3-5 microns, and the speed was 50-1200r / min for 0.5-5h. After grinding, microfiltration was performed through a microporous filter membrane to obtain a filtrate of a micron-scale nanocomposite antibacterial agent solution;
[0216] S2. The micron-sized nanocomposite antibacterial agent solution obtained in step S1 is subjected to a nano-sized zirconium oxide sand mill at a speed of 50-3300 r / min for 1-10 h, and the sand milling is stopped after the particle size is detected to be 50-100 nm, and the filtrate is filtered with an ultrafiltration membrane to obtain a nanocomposite antibacterial agent solution;
[0217] S3. The nanocomposite antibacterial agent solution obtained in step S2 is dried by a nano-scale spray dryer at a pressure of 10-70MPa and a temperature of 90°C-120°C to obtain a nanocomposite antibacterial agent;
[0218] S4. Add 5 parts of silica gel, 5 parts of zeolite, 3 parts of kaolin and 40 parts of ultrapure water to a food-grade coating-type horizontal zirconia three-roll mill, adjust the roller pitch to 3-5 microns, grind at a speed of 50-1200r / min for 0.5-5h, and after grinding, microfiltration was performed through a microporous membrane to obtain a filtrate obtained as a micron-sized organic gas adsorption material solution;
[0219] S5. The micron-sized organic gas adsorption material solution obtained in step S4 is subjected to a nano-sized zirconium oxide sand mill at a speed of 50-3300 r / min for 1-8 h, and after grinding, the solution is filtered and separated through an ultrafiltration membrane to obtain a nano-sized organic gas adsorption material solution;
[0220] S6. The nanoscale organic gas adsorption material solution obtained in step S5 is dried in a nanoscale spray dryer at a pressure of 15-80MPa and a temperature of 85°C-120°C to obtain a nanoscale organic gas adsorption material;
[0221] S7. The nanocomposite antibacterial agent obtained in step S3 above, 15 parts, the nanoscale organic gas adsorption material obtained in step S6, 13 parts, were stirred and dispersed in a high-speed stirrer at a stirring speed of 500-2500r / min for 5-60min to obtain a mixed material A;
[0222] S8. 40 parts of ultrapure water, 6 parts of aqueous pure acrylate emulsion, 7 parts of acrylic acid-acrylic acid copolymer modified emulsion, 2 parts of hydroxypropyl cellulose, 0.2 parts of acrylic acid copolymer, and 0.6 parts of glycerol were added to the reactor for thorough mixing and dispersion, with a stirring speed of 100-800 r / min for 15-20 min. After stirring, the mixture was microfiltered through a microporous filter membrane to remove large particles to obtain a mixed material B solution;
[0223] S9. 0.3 parts of alkyl-modified silicone oil, 0.3 parts of butyl octadecanoate, 0.3 parts of cetearyl alcohol polyether, 0.5 parts of sodium succinate octyl sulfonate, 0.5 parts of sorbitan tristearate, 0.5 parts of polyoxyethylene sorbitan monostearate, 0.4 parts of sodium dodecylbenzene sulfonate, 0.3 parts of polydimethylsiloxane, 0.2 parts of dodecanol, 0.2 parts of polyurethane leveling agent, and 0.5 parts of organic-acetylene defoaming agent are added to a vertical vortex liquid-liquid mixer, and the mixture is stirred and mixed for 15-60 minutes at a speed of 100-1800 r / min, a vortex intensity of 0.5-3 m / s, and a temperature of 5-30° C. to obtain a mixed solution C;
[0224] S10. Add the mixed material A obtained in step S7 and the mixed material B solution obtained in step S8 to a horizontal zirconia vortex solid-liquid mixer, and stir and mix at a speed of 100-2000 r / min, a vortex intensity of 0.3-3.2 m / s, and a temperature of 5-30°C for 1-6 hours to obtain a mixed solution D;
[0225] S11. Add the mixed solution D of step S10 into a nano-sized zirconium oxide sand mill, grind and disperse at a speed of 50-3300 r / min for 0.5-10 h, and add the mixed solution C obtained in step S9 into five equal portions for five times during the grinding process. After grinding, separate the mixture by filtering with a nanofiltration membrane, and bucket the filtrate to obtain a water-based masterbatch.
[0226] S12. Place the water-based masterbatch obtained in step S11 in the barrel of an automatic sprayer and set the parameters of the automatic sprayer;
[0227] S13. The automatic spraying machine uses an ultra-fine atomizing nozzle with an aperture of 0.05mm-0.1mm. The spraying angle of the ultra-fine atomizing nozzle for spraying the surface of the pulp molded packaging product is set to 80°-100°, and the spraying angle of the ultra-fine atomizing nozzle for spraying the left and right sides is set to 15°-45°. The three nozzles are connected in parallel on the same track, and the moving speed of the spray gun is set to 3-10m / min.
[0228] S14. Further, the spraying distance is set to 15-25 cm and the spraying pressure is set to 3-8 bar;
[0229] S15. Further, the slurry flow rate is set to 30-200mL / min, and the spraying thickness is set to 3-60um;
[0230] S16. Further, the oven temperature is set to 80-120°C, and the drying time is set to 10-180s;
[0231] S17. Start the automatic spraying machine to evenly spray the water-based masterbatch on the inner surface of the pulp molded packaging product, and obtain the pulp molded packaging product after even film formation and drying.
[0232] Comparative Example 8
[0233] Blank pulp molded packaging product.
[0234] The particle size of the nanocomposite antibacterial agent was tested using Malvern Mastersizer 3000 laser particle size analyzer LPSA. The average value was taken after 10 tests. The test results are shown in Table 1.
[0235] Table 1 Test results of particle size of water-based masterbatch with fresh-keeping function
[0236]
[0237]
[0238] According to the particle size test results, the particle size of the fresh-keeping functional water-based masterbatch is within 0.1-50nm, among which Dv(50) is 18.4nm and Dv(90) is 32.8nm, that is, the main particle size of the fresh-keeping functional water-based masterbatch is distributed within 0.1-50nm.
[0239] The nozzle clogging results of the above-mentioned Example 1, Example 2, and Comparative Examples 1-7 during spraying are shown in Table 2.
[0240] Table 2 Comparison of nozzle blockage results
[0241]
[0242] According to the results in Table 2, when the particle size exceeds 0.1-50nm, the nozzle of the automatic spraying machine will be slightly blocked, affecting the continuous operation of production and having an adverse effect on production efficiency. At the same time, if the nano-composite antibacterial agent or organic gas adsorbent is not ground, the particle size is too large and the nozzle will be blocked.
[0243] The pulp molded packaging products of Example 1, Example 2, and Comparative Examples 1-8 were cut according to GB / T31402-2015, and the antibacterial properties of Example 1, Example 2, and Comparative Examples 1-8 were tested. Each case was tested 10 times and the average value was taken. The test results are shown in Table 3.
[0244] Table 3 Comparison of antibacterial effects
[0245]
[0246] According to the results in Table 3, when the nano-composite antibacterial agent is added and ground and dispersed with the water-based resin, the nano-composite antibacterial agent can be effectively dispersed in the water-based masterbatch with fresh-keeping function by adjusting the applicable viscosity and adding the corresponding food-grade dispersant. And the surface of the nano-composite antibacterial agent is modified by a surfactant to enhance the antibacterial activity. At the same time, the particle size distribution range of the nano-composite antibacterial agent is relatively wide, and multiple particle sizes work synergistically. The antibacterial effect of the prepared fresh-keeping functional coating is significantly improved compared with the antibacterial effect of the coating with a narrow particle size distribution range and a single particle size. Then the nano-composite antibacterial agent is loaded on the ground nano-scale organic gas adsorption material, and the antibacterial effect of the prepared fresh-keeping functional coating is better. And after the materials are ground and sanded separately, the nano-composite antibacterial agent has a better effect in the whole and a higher antibacterial rate.
[0247] The organic gas adsorption rates of the pulp molded packaging products of Example 1, Example 2, and Comparative Examples 1-8 were tested with reference to GB21551.4-2010. Each case was tested 10 times and the average value was taken. The test results are shown in Table 4.
[0248] Table 4 Comparison of organic gas adsorption effects
[0249]
[0250] According to the results in Table 4, when the organic gas adsorption material is ground into nano-scale effective dispersion, the prepared fresh-keeping coating has significantly improved organic gas adsorption effect compared with no addition of organic gas adsorption material and no sanding of the organic gas adsorption material.
[0251] The water leakage of the pulp molded packaging products of Example 1, Example 2, and Comparative Examples 1-8 was tested with reference to GB / T36787-2018. Each case was tested 10 times and the average value was taken. The test results are shown in Table 5.
[0252] Table 5 Comparison of water leakage and long-term water resistance
[0253]
[0254] According to the comparison results in Table 5, the pulp molded packaging products with preservation effect treated with emulsifier and wetting agent can effectively prevent water leakage, while the blank pulp molded packaging products have serious water seepage. When the water-based masterbatch with preservation function is sprayed on the inner surface of the pulp molded packaging products, it can effectively prevent the moisture generated by the respiration and transpiration of fruits and vegetables from penetrating into the fibers of the pulp molded packaging products and causing damage, thereby protecting the pulp molded packaging products.
[0255] The pulp molded packaging product with preservation effect of the present invention and the blank pulp molded packaging product were tested for preservation of sweet potato leaves, and 5 groups of tests were set up. After being placed at room temperature for 3 days, the decay rate, weight loss rate and yellowing rate were tested. The test results are shown in Table 6.
[0256] Table 6 Comparison of sweet potato leaf test results
[0257] Test items Coated pulp molded packaging products with preservation effect Blank pulp molded packaging products Decay rate / % 2.68 72.83 Weight loss rate / % 3.42 33.96 Yellowing rate / % 4.57 86.54
[0258] According to the comparison results in Table 6, pulp molded packaging products with preservation effects can effectively inhibit bacterial growth; effectively retain water for fruits and vegetables, so that the fruits and vegetables remain upright and have better appearance; and absorb organic gases produced by fruits and vegetables, which has the effect of preserving green and maintaining appearance, thereby extending the shelf life of fruits and vegetables.
[0259] Although the technical solutions of the present invention have been described and listed in detail, it should be understood that it is obvious to those skilled in the art to make modifications to the above embodiments or adopt equivalent alternatives. These modifications or improvements made without departing from the spirit of the present invention are within the scope of protection required by the present invention.
Claims
1. A water-based masterbatch with fresh-keeping function suitable for pulp molding, characterized in that: The fresh-keeping functional water-based masterbatch comprises the following components in parts by mass:
2. The water-based masterbatch with fresh-keeping function suitable for pulp molding according to claim 1, characterized in that: The water-based resin is at least one or more of acrylate emulsion, water-based pure acrylate emulsion, acrylic acid-acrylate copolymer emulsion, and acrylic acid-acrylic acid copolymer modified emulsion.
3. The water-based masterbatch with fresh-keeping function suitable for pulp molding according to claim 1, characterized in that: The nano composite antibacterial agent is at least one or more of nano titanium dioxide, magnesium silicate, sorbic acid, sodium boric oxide, borax, methyl parahydroxybenzoate and sodium thiosulfate.
4. The water-based masterbatch with fresh-keeping function suitable for pulp molding according to claim 1, characterized in that: The organic gas adsorption material is at least one or more of silicon dioxide, modified starch, silica gel, zeolite, sodium magnesium lithium silicate, and kaolin.
5. The water-based masterbatch with fresh-keeping function suitable for pulp molding according to claim 1, characterized in that: The viscosity modifier is at least one or more of bentonite, ethyl cellulose, hydroxyethyl cellulose and hydroxypropyl cellulose.
6. The water-based masterbatch with fresh-keeping function suitable for pulp molding according to claim 1, characterized in that: The dispersant is at least one or more of acrylic acid copolymer and glycerol; The lubricant is at least one or more of alkyl-modified silicone oil, butyl octadecanoate, and polyacrylamide; The surfactant is at least one or more of cetearyl alcohol polyether, ethoxylated castor oil, and sodium octyl succinate sulfonate; The emulsifier is at least one or more of sorbitan tristearate, polyoxyethylene sorbitan monostearate, and polyoxyethylene sorbitan tristearate; The wetting agent is at least one or two of sodium dodecylbenzene sulfonate and polydimethylsiloxane.
7. The water-based masterbatch with fresh-keeping function suitable for pulp molding according to claim 1, characterized in that: The leveling agent is at least one or more of dodecanol, polyethylene glycol, and polyurethane leveling agents; The defoaming agent is at least one or two of an organosilicon defoaming agent and an organic-acetylene defoaming agent.
8. The water-based masterbatch with fresh-keeping function suitable for pulp molding according to claim 1, characterized in that: The average particle size of the fresh-keeping functional water-based masterbatch suitable for pulp molding is 0.1-50 nm.
9. A method for preparing a water-based masterbatch with a fresh-keeping function suitable for pulp molding as claimed in any one of claims 1 to 8, characterized in that: The method comprises the following steps: S1. The nano-composite antibacterial agent and ultrapure water were added to a food-grade coating-type horizontal zirconia three-roll mill, the roller pitch was adjusted to 3-5 microns, and the speed was 50-1200r / min for grinding for 0.5-5h. After grinding, the microfiltration was performed through a microporous membrane, and the filtrate was a micron-grade nano-composite antibacterial agent solution; S2. The micron-sized nanocomposite antibacterial agent solution obtained in step S1 is subjected to a nano-sized zirconium oxide sand mill at a speed of 50-3300 r / min for 1-10 h, and the sand milling is stopped after the particle size reaches the standard of 0.1-50 nm, and the filtrate is filtered and separated with an ultrafiltration membrane to obtain a nanocomposite antibacterial agent solution; S3. The nanocomposite antibacterial agent solution obtained in step S2 is dried by a nano-scale spray dryer at a pressure of 10-70MPa and a temperature of 90°C-120°C to obtain a nanocomposite antibacterial agent; S4. The organic gas adsorbent material and ultrapure water were added to a food-grade coating-type horizontal zirconia three-roll mill, the roller pitch was adjusted to 3-5 microns, and the speed was 50-1200r / min for grinding for 0.5-5h. After grinding, the microporous membrane was microfiltered to obtain a micron-sized organic gas adsorbent solution; S5. The micron-sized organic gas adsorption material solution obtained in step S4 is subjected to a nano-sized zirconium oxide sand mill at a speed of 50-3300 r / min for 1-8 h, and after grinding, the solution is filtered and separated through an ultrafiltration membrane to obtain a nano-sized organic gas adsorption material solution; S6. The nanoscale organic gas adsorption material solution obtained in step S5 is dried in a nanoscale spray dryer at a pressure of 15-80MPa and a temperature of 85°C-120°C to obtain a nanoscale organic gas adsorption material; S7. The nanocomposite antibacterial agent obtained in step S3 and the nanoscale organic gas adsorption material obtained in step S6 are stirred and dispersed in a high-speed stirrer at a stirring speed of 500-2500 r / min for 5-60 min to obtain a mixed material A; S8. Ultrapure water, water-based resin, viscosity modifier and dispersant were sequentially added to the reactor for thorough mixing and dispersion, with a stirring speed of 100-800 r / min for 15-20 min, and then stirred and microfiltered through a microporous membrane to remove large particles to obtain a mixed material B solution; S9. Add lubricant, surfactant, emulsifier, wetting agent, leveling agent and defoamer to a vertical vortex liquid-liquid mixer, stir and mix for 15-60 min at a speed of 100-1800 r / min, a vortex intensity of 0.5-3 m / s and a temperature of 5-30° C. to obtain a mixed solution C; S10. Add the mixed material A obtained in step S7 and the mixed material B solution obtained in step S8 to a horizontal zirconia vortex solid-liquid mixer, and stir and mix at a speed of 100-2000 r / min, a vortex intensity of 0.3-3.2 m / s, and a temperature of 5-30°C for 1-6 hours to obtain a mixed solution D; S11. Add the mixed solution D of step S10 into a nano-scale zirconium oxide sand mill, grind and disperse at a speed of 50-3300 r / min for 0.5-10 h, and add the mixed solution C obtained in step S9 into five equal parts five times during the grinding process. After grinding, filter and separate through a nanofiltration membrane, and bucket the filtrate to obtain a water-based masterbatch with a fresh-keeping function suitable for pulp molding.
10. An application of a water-based masterbatch with a fresh-keeping function suitable for pulp molding as claimed in any one of claims 1 to 8, characterized in that: The water-based masterbatch with fresh-keeping function suitable for pulp molding is used to prepare pulp molding packaging products with fresh-keeping function, and the specific steps are as follows: S12. Place the water-based masterbatch with fresh-keeping function obtained in step S11 in the barrel of the automatic sprayer, and set the parameters of the automatic sprayer; S13. The automatic spraying machine uses an ultra-fine atomizing nozzle with an aperture of 0.05mm-0.1mm. The spraying angle of the ultra-fine atomizing nozzle for spraying the plane of the pulp molded packaging product is set to 80°-100°, and the spraying angle of the ultra-fine atomizing nozzle for spraying the left and right sides is set to 15°-45°. The three nozzles are connected in parallel on the same track, and the movement speed of the spray gun is set to 3-10m / min; S14. Further, the spraying distance is set to 15-25 cm and the spraying pressure is set to 3-8 bar; S15. Further, the slurry flow rate is set to 30-200mL / min, and the spraying thickness is set to 3-60um; S16. Further, the oven temperature is set to 80-120°C, and the drying time is set to 10-180s; S17. Start the automatic spraying machine to evenly spray the water-based masterbatch with fresh-keeping function on the inner surface of the pulp molded packaging product, and obtain the pulp molded packaging product with fresh-keeping function after uniform film formation and drying.